Kajian Penilaian Risiko Kesehatan terkait Pajanan BTX Mengacu pada Metode SQRA di Laboratorium Pengujian Migas PT.X - Rachmawan, Ryan; Tejamaya, Mila (National Journal of Occupational Health and Safety, 2021)
The laboratory is an experimentation or testing workplace that requires careful behavior in using equipment and material. One of the types of chemicals in the laboratory is an organic solvent as a solvent for other chemicals. The potential risk of breast cancer in female laboratory workers in this cohort study is exposure to organic solvents. Organic solvents that are often used in the laboratory are benzene, toluene, and xylene (BTX). Given workplace exposure to the chemicals benzene, toluene, and xylene, as well as the health hazards posed by these chemicals, a health risk assessment by inhalation using the Singapore SQRA technique is required to assess the amount of risk of chemical exposure to the health of workers at PT. X. Using a questionnaire that corresponds to The German Q18 Questionnaire to collect data on the health complaints of laboratory employees with neurotoxic symptoms. Inhalation and air sampling in the workplace were the first steps in the research. Data from sampling is analyzed to establish the degree of hazard (Hazard Rating), exposure (Exposure Rating), and risk (Risk Rating). Benzene, toluene, and xylene exposure levels were 1.6, 2.0, and 2.1, respectively. Benzene has a danger rating of 3 (moderate), while toluene and xylene have a risk rating of 2 (low risk). In terms of the percentage of respondents with positive neurotoxic symptoms or who answered "yes" to five or more questions on the questionnaire, 25% (1 respondent) and 75% (3 respondents) had negative neurotoxic symptoms.